MEMOTRET KESEMPURNAAN INSAN MENURUT FILSAFAT JIWA IBN SĪNĀ - Nurul Khair (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2020)
This paper aims to offer a new perspective on understanding human perfection throughIbn Sīnā’s philosophical framework which is seen as being able to correct the mistakes ofwestern philosophers. It is known that Sigmund Freud and Thomas Hobbes understoodhuman existence physically. As a result, the soul which is seen as the substance of humanexistence is seen as materialistic which can be measured materially to achieve perfectionin reality. The implication is that human perfection is also seen as partially. Partialperfection does not explain the value, dignity and happiness of humans universally, so theviews of Sigmund Freud and Thomas Hobbes do not lead humans to holistic perfection, ashuman nature wants absolutes. In order to overcome the paradigm of Sigmund Freud andThomas Hobbes, this paper explores human perfection according to Ibn Sīnā’s philosophyof the soul through one of his magnumopuses, entitled Mabda wa al-Ma’ad. By using adescriptive-philosophical method, the conclusion is that Ibn Sīnā examines the existenceof the soul through a transcendental approach. According to Ibn Sīnā, the existence ofthe soul cannot be perceived through the senses. Conversely, the existence of the soulcan be known through human awareness of correct knowledge, called ma’rifatal-Ḥaqto systematize various human behavior, called ma’rifat al-khair. Human understandingof ma’rifat al-Ḥaq and ma’rifat al-khair will guide him towards holistic perfection, bothparadigmatically and behaviorally.